Internal load, external load and the pole force ration (PFR) in cross-country skiing - Kuylenstierna, D. (Skisens, 2025)
There are several different ways to quantify the load the body is exposed to during physical exercise. These can be divided into measures of internal load and external load. Internal load refers to how hard the body is working, while external load refers to the work performed by the body.